CHANGE OF CONTRACT OF AN EMPLOYEE DUE TO TRANSFER TO ANOTHER JOB (American Journal of Technology and Applied Sciences, 2025)
The employee shall not be transferred to another job if there are contraindications for the employee based on his/her health status, confirmed by a medical report.When transferring an employee to another job, the date by which he/she must begin the work he/she is transferred to must be determined.